MAN, GOD AND MANDALA - Overzee, Anne Hunt (Journal of Dharma, 1985)
Man, born in this world, is in search of truth. Truth is reality which is all and whole. The praying man is actually in search of this all and whole, struggling to liberate himself from the sea of time and transience. Accordingly religions developed world-visions, darsanas or weltanschauung, which present to their respective followers the totality of reality in due order. The traditional pattern of the presentation of a particular world-vision in a diagram is known in India as mandala. India developed mandalas from very ancient times. In one way or another, they are also used in several Western traditions. Mandalas give us the total reality in one glimpse, make us realize where we are in the great divine plan of cosmic salvation and whither we are now heading for. Thus mandala becomes a great help for meditative prayer.